Analisis Dampak Pembangunan Infrastruktur Jalan terhadap Pertumbuhan Ekonomi Kecamatan Medan Tembung - Zahra, Karin; Riris Hotma Roito Manalu; Rana Nabillah; Putri Kemala Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research was to see the role of highways in the economic development of the Medan Tembung sub-district. This research is a qualitative type of research with a data collection method by conducting interviews. The method used in preparing this journal is a descriptive method through literature review and literature review. Journal preparation is carried out through literature review, namely by analyzing and reviewing books and scientific journals that have been published. The results of the research show that the development of road infrastructure has a significant and significant impact on the economic growth of the Medan Tembung sub-district community. Highway construction opens up new opportunities for communities that support economic growth.